Manipulation of magnetic nanostructures through low temperature metal-oxygen chemistry: Co/CoO exchange biased nanodonuts and Co nanotips - Phase, Deodatta; Choudhary, Ram Janay; Ganesan, V.; Reddy, V. Raghvendra; Gupta, Ajay; Selvi, N.; Kulkarni, Sneha; Ogale, Satishchandra (Solid State Communications, 2009)
Dense nanodonut and nanotip type morphologies are shown to self-evolve in Ultrathin cobalt films during growth under Vacuum, depending oil the level of oxygen incorporation and temperature. The nanodonut morphology forms at room temperature and the corresponding magnetic hysteresis shows exchange bias (similar to 35 Oe shift along the field axis), which is attributed to the presence of CoO and its exchange Coupling with cobalt. The morphology evolves into nanotip features with increase of growth temperature, with Concurrent elimination of the oxide component and exchange bias. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Co/CoO; Magnetic film; self assembly; Vacuum evaporation

Colossal thermoelectric power in Gd-Sr manganites - Sagar, S.; Ganesan, V.; Joy, Pattayil Alias; Thomas, Senoy; Liebig, A.; Albrecht, M.; Anantharaman, Maliemadom R. (EPL, 2010)
Manganites belonging to the series Gd(1-x)Sr(x)MnO(3) (x=0.3, 0.4 and 0.5) were prepared by wet solid-state reaction and their thermoelectric power was evaluated. Thermoelectric power measurements revealed a peak value at similar to 40 K. All the samples exhibited a colossal thermopower at similar to 40K and in that Gd(0.5)Sr(0.5)MnO(3) exhibited a maximum value of similar to 35 V/K, which is the largest reported for these class of materials at this temperature. Temperature-dependent magnetisation measurements showed that the samples exhibit a phase transition from paramagnetic to spin-glass-like state at these temperatures. Plausible mechanisms responsible for the observed colossal thermoelectric power in Gd-Sr manganites are discussed. Copyright (C) EPLA, 2010

Electrochemically synthesized faceted CuInTe2 nanorods as an electron source for field emission applications - Lakhe, Manorama G.; Joshi, Padmshree; Choudhary, Ram J.; Ganesan, V.; Joag, Dilip S.; Chaure, Nandu B. (New Journal of Chemistry, 2018)
Herein, CuInTe2 (CIT) thin films with faceted nanorod-like morphology have been synthesized on a flexible molybdenum foil using a water-based low-cost electrodeposition technique. The co-deposition potential for CIT was optimized using cyclic voltammetry with respect to that of the Ag/AgCl reference electrode, and films were deposited from -0.6 V to -0.9 V at the working temperature of 75 degrees C. The as-prepared CIT films exhibited an amorphous nature, whereas the RTP-annealed films exhibited a highly crystalline chalcopyrite nature as a function of the growth potential. A red shift was observed in the Raman spectra of the as-deposited films that shifted towards the original position upon annealing. The Cu/In ratio obtained by the EDS analysis was found to decrease systematically upon increasing the growth potential. X-ray photoelectron spectroscopy (XPS) studies revealed the presence of Cu+, Cu2+ satellites, In3+, Te2-, and Te4+ states of Cu, In, and Te. The field emission study showed a maximum current density of 1.74 mA cm(-2), which was attainable at an applied electric field of 1.5 V mu m(-1). The turn-on field was found to be 0.92 V mu m(-1), comparable to that of the carbon nanofibres. The emitter exhibited stable electron emission over a period of 3 hours. The faceted CIT nanorods with columnar growth are a potential candidate for application as an electron source, and herein, the field emission of CIT nanorods is reported for the first time.